2008
DOI: 10.1371/journal.pgen.1000012
|View full text |Cite
|
Sign up to set email alerts
|

ruvA Mutants That Resolve Holliday Junctions but Do Not Reverse Replication Forks

Abstract: RuvAB and RuvABC complexes catalyze branch migration and resolution of Holliday junctions (HJs) respectively. In addition to their action in the last steps of homologous recombination, they process HJs made by replication fork reversal, a reaction which occurs at inactivated replication forks by the annealing of blocked leading and lagging strand ends. RuvAB was recently proposed to bind replication forks and directly catalyze their conversion into HJs. We report here the isolation and characterization of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 62 publications
5
43
0
Order By: Relevance
“…2B). The inability of RuvAz mutants to protect the HJ from RuvC cleavage confirms that they form unstable complex II (29). These results also suggest that a tetramer of RuvA bound to the HJ (complex I) does not inhibit HJ cleavage by RuvC, and it is possible that both RuvA and RuvC bind together to the junction.…”
Section: Ruva2 Kap Binds Efficiently To Holliday Junctions As a Singlementioning
confidence: 58%
See 4 more Smart Citations
“…2B). The inability of RuvAz mutants to protect the HJ from RuvC cleavage confirms that they form unstable complex II (29). These results also suggest that a tetramer of RuvA bound to the HJ (complex I) does not inhibit HJ cleavage by RuvC, and it is possible that both RuvA and RuvC bind together to the junction.…”
Section: Ruva2 Kap Binds Efficiently To Holliday Junctions As a Singlementioning
confidence: 58%
“…Stability of RuvA2 KaP Complex II in Solution-In vivo RuvC cannot function without RuvAB (7,8,29,30); however, it has been shown that formation of RuvA complex II occludes the HJ and prevents RuvC-mediated cleavage in vitro (26,31,32). To assess the stability of the RuvA2 KaP complex II in the presence of Mg 2ϩ , we compared the ability of both wild type and mutant proteins to protect a HJ from cleavage by RuvC (Fig.…”
Section: Ruva2 Kap Binds Efficiently To Holliday Junctions As a Singlementioning
confidence: 99%
See 3 more Smart Citations